Bioactives and Antioxidant Activities of Marigold Flower Juices and the Effect of Different Storage Times - Phuseerit, Onanong; Wrigley, Colin; Siriamornpun, Sirithon (Food Agricultural Sciences and Technology, 2021)
The aim of this research was to investigate changes in phenolic compounds, carotenoids and antioxidant activities in marigold flower (Tagetes erecta L.) juice with vitamin added and different storage times. The samples were stored for four weeks at 4 °C. The results of this study indicated that changes in the levels of carotenoids, phenolic compounds and the antioxidant activity in marigold juice were affected by storage period. The carotenoids (lycopene, β-carotene and lutein) and total flavonoid contents decreased during the storage period. Total phenolic contents increased during storage for three weeks’ storage under the same conditions, but had declined by the end of the storage period (four weeks). The phenolic acids found were ferulic acid and sinapic acid; the level of each increased during storage while, other phenolic acids and flavonoids decreased during storage. For antioxidant activity (DPPH assay), there was a slight increase in marigold juice with added vitamin E and with a combination of vitamin C and vitamin E. On the other hand, antioxidant activity decreased in marigold juice (no vitamin additives) and in marigold juice with added vitamin C. The present study has provided useful information for industrial production of edible flower juice.